L' "Ufficio Della Passione Del Signore": Contemplare e celebrare il piano di salvezza - Molina, Bernardo (Miscellanea francescana, 2024)
This study explores the importance of the Office of the Passion of the Lord, composed by Francis of Assisi, as an expression of contemplation and celebration of the mystery of salvation. After a brief introduction on the historicalcritical aspects, the fifteen psalms chosen by Francis are analysed, highlighting their liturgical and spiritual meaning. The article also examines the antiphon and the final acclamation, emphasising the Marian and Trinitarian dimension of the Office. It concludes with a reflection on the theological-spiritual perspectives, highlighting the centrality of the Paschal Mystery.